Improving the Quality of Public Services Through Bureaucratic Reform at the Gunungsari District Office - Huddori, Huddori; Su’amah, Su’amah; Widayanti, Sri; Hendayani, Bq; Kartini, Kartini (Visi Pencerah Nusantara, 2025)
This study aims to determine and analyze Bureaucratic Reform in Public Services at the Gunungsari District Office, West Lombok Regency, West Nusa Tenggara. The research method employed is qualitative, utilizing a case study approach. The theory used by the author is based on the guidelines outlined in Komarudin (2014:268), which include